Eco-friendly bio-epoxy coatings for corrosion-resistant and easy-cleaning applications - Toh, Sen Hou (2019)
Epoxy resin is one of the most important components of superhydrophobic coatings, due to its excellent properties. However, around 90% of the epoxy resin produced worldwide is diglycidyl ether of bisphenol A (DGEBA), deriving from bisphenol A (BPA) and epichlorohydrin. As is well known, BPA contributing more than 67% of the molar mass of DGEBA, is mainly from fossil resources and is proven to be harmful to human health especially on endocrine system. Hence the focus of this project is the development of Isosorbide-epoxy resins as an ecofriendly-replacement to bisphenol A(BPA) in the formulation of hydrophobic coatings. To prepare the hydrophobic coating from hydrophilic Isosorbide resins, a suitable curing agent and hydrophobic modifier is required. To evaluate the technique of synthesizing hydrophobic coatings from the spin coating method, samples are prepared with different formulation and parameters, such as the mixing time and the amount of silicon dioxide nanopowder (SiO2). These samples were then characterized through their water contact angle (WCA), their sliding angle (SA) and electrochemical resistance tests to evaluate the wettability, thermal and mechanical properties of the coating produced. The effect of a superhydrophobic coating in self-cleaning and its corrosion resistance properties were also studied. A superhydrophobic coating was achieved with a contact angle of 153.1 degree by optimizing the parameters. Furthermore, the samples were enhanced to display even better properties through infusing silicon fluid to the coating to produce self-slippery liquid-infused porous surfaces which showed even better properties with a very low sliding angle of 0-1degrees and a higher resistance to corrosion, Finally, some challenges and potential future work recommendations will also be discussed.